Manajemen Mutu di Koperasi Wanita Bunga Tanjung - Ma’mun, Saepul; Setiadi, Kusmara; Solihin, Dadin; Herlan Sudrajat, Uep (Jurnal Etnik: Ekonomi-Teknik, 2022)
Cooperative quality management has the task of raising, collecting, coordinating, and developing its potential so that it becomes a power to improve the standard of living of its members. The problems studied are regarding the management system of the Tanjung Flower Women's Cooperative that is run, the implementation of management, and the impact of management on improving performance. The purpose describes analyzing the management of the Tanjung Flower Women's Cooperative. This research is descriptive qualitative with data mining techniques carried out with an observation approach, interviews, and reference studies based on data analysis, display, and verification. The results showed that the management system of the Putri Bunga Tanjung Women's Cooperative was not optimal, the indications from implementing policies were still situational, performance management still had weaknesses regarding job descriptions, documentation of activities that had not been systematic based on SOM, and SOP, as well as securing documents. The implementation dimension has not been run by the management function, especially as stated in the vision, mission, and objectives.  Organizing, generally, has gone well according to AD-ART. But management control and evaluation have not been carried out optimally. The indicators can be seen from the performance of working capital management, management functions, and management involvement with stakeholders.